Evaluation of ammoniated wheat straw in receiving and growing diets - Schlegel, Ethan R. (Kansas State University, 2015)
Drought conditions in the past have created a shortage of prairie hay and other grass hays that are used as roughage sources for receiving and growing beef diets. Historically, wheat straw and other cereal crop residue has been discounted as a feedstuff due to its low nutrient content. Chemical methods, including ammonia application, can improve the feeding value of cereal crop residue while constraining costs. While there are studies that show the efficacy of utilizing ammoniated wheat straw in beef cow and maintenance diets, limited data are available characterizing the feeding value of ammoniated wheat straw in receiving and growing diets. The objective of these two studies were to evaluate cattle growth and diet digestibility for receiving and growing diets containing either wheat straw (STRW), anhydrous ammonia treated wheat straw (AMMN), or a prairie hay and alfalfa blend (CONT) at 30% inclusion. Exp. 1 utilized 288 crossbred steers (271 kg) randomized to 8 pens per treatment and fed their respective test diets for 56 d and a common diet for 14 d to equalize gastrointestinal tract fill. No effect of straw ammoniation was observed on final bodyweight (BW), average daily gain (ADG), dry matter intake (DMI), or gain to feed (G:F) (P > 0.31). The 56-d BW, ADG, and G:F for CONT were significantly different from both STRW and AMMN (P < 0.001). Exp. 2 utilized 6 ruminally fistulated Holstein heifers (288 kg) in a replicated 3 × 3 Latin square design. There were no observed differences between AMMN and STRW in dry matter (DM), organic matter (OM), or ADF intake (P > 0.57) although CONT differed significantly from both straw treatments in DM, OM, and ADF intake (P < 0.05). Digestibility of DM, OM, and ADF were not different between AMMN and STRW (P > 0.43), where as CONT and STRW were different (P < 0.05). Anhydrous ammonia treatment of wheat straw had no effect on ruminal VFA concentration (P > 0.32). Ruminal pH was not affected by anhydrous ammonia application (P = 0.32), but STRW and CONT were different (P < 0.05). Fluid passage rate was not different among the three treatments (P = 0.33). Wheat straw is a suitable replacement for ammoniated wheat straw at 30% inclusion in receiving and growing diets that contain 40% of dietary DM as wet corn gluten feed. Further research is necessary to determine the effect of varying levels of wheat straw and ammoniated wheat straw in conjunction with wet corn gluten feed and other by-product feeds in receiving and growing diets in order to capitalize on performance and efficiency gains while constraining costs.
Keywords: Beef cattle; Cereal crop; Growth; Wheat straw; Ammoniation; Nutrition; Animal Sciences (0475)